When two ‘wrongs’ make a right: An essay on business ethics - Kavka, Gregory S. (Journal of business ethics, 1983)
Sometimes two wrongs do make a right. That is, others' violations of moral rules may make it permissible for one to also violate these rules, to avoid being unfairly disadvantaged. This claim, originally advanced by Hobbes, is applied to three cases in business. It is suggested that the claim is one source of scepticism concerning business ethics. I argue, however, that the conditions under which business competitors' violations of moral rules would render one's own violations permissible are quite restricted. Hence, the observation that two wrongs may make a right does not give people a broad warrant for ignoring moral standards in their business activities.